Resin composition for benzocyclobutenyl cyclotriphosphazene copper-clad plate as well as preparation method and application of resin composition
The halogen-free flame-retardant copper clad plate is prepared by copolymerizing benzocyclobutenyl cyclotriphosphazene with hydrocarbon resin, which solves the problem of insufficient flame-retardant performance of hydrocarbon resin copper clad plate, and achieves excellent dielectric and heat resistance of high-frequency signal transmission.
Patent Information
- Application Number
- CN202510439465.5
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-04-09
- Publication Date
- 2025-08-26
AI Technical Summary
The existing hydrocarbon resin copper clad plates have insufficient flame retardant performance in high-frequency signal transmission, poor heat resistance, low glass transition temperature, insufficient rigidity and large thermal expansion coefficient, which cannot meet the requirements of high-frequency and high-speed copper clad plates.
Benzocyclobutenyl cyclotriphosphazene interacts with hydrocarbon resin, improves cross-linking density and molecular structural rigidity through copolymerization reaction, and adds a synergistic flame retardant agent to prepare halogen-free flame-retardant copper clad plate.
It achieves high-efficiency halogen-free flame retardant, excellent dielectric properties, heat resistance and mechanical properties, dielectric constant 2.49-2.53, dielectric loss 0.0010-0.0013, glass transition temperature 209-221℃, peel strength 1.41-1.47N/mm, thermal expansion coefficient <50ppm.
Smart Images

Figure BDA0005350611560000021 
Figure BDA0005350611560000051 
Figure BDA0005350611560000052
Abstract
Description
Technical Field
[0001] The present invention belongs to the field of electronic resin synthesis, and particularly relates to a resin composition for a benzocyclobutenylcyclotriphosphazene copper-clad laminate, a preparation method and an application thereof. Background Art
[0002] With the rapid development of industries such as artificial intelligence large-scale integrated circuits (AIGC), machine learning, 5G communications, millimeter-wave radar, and the Internet of Things, the frequency of signal transmission on printed circuit boards (PCBs) is increasing. High-frequency and high-speed copper-clad laminates (CCLs) have become a research hotspot in the PCB industry. To reduce transmission losses in high-frequency bands while also being able to handle the high-temperature soldering and multi-layer assembly requirements during substrate installation, the insulation materials used in CCLs must be halogen-free and flame-retardant, with superior dielectric properties, heat resistance, glass transition temperature, and dimensional stability.
[0003] In recent years, hydrocarbon resins such as polybutadiene resin, styrene-butadiene copolymer, ethylene propylene diene monomer copolymer, and cycloolefin copolymer have attracted much attention due to their low molecular chain polarity (electronegativity of carbon and hydrogen atoms is 2.5 and 2.1, respectively) and excellent dielectric properties (dielectric constant 2.4-2.8 at 1 MHz, tanδ 0.0002-0.0006). However, these hydrocarbon resins have poor flame retardancy, extremely flexible chains, and poor adhesion to substrates. Copper-clad laminates made from them also have disadvantages such as poor heat resistance, low glass transition temperature, insufficient rigidity, and a large thermal expansion coefficient. Summary of the Invention
[0004] The present application aims to overcome the deficiencies in the prior art and provides a benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates, a preparation method thereof, and an application thereof. The benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates provided by the present invention can provide the benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates with good flame retardant properties, dielectric properties, heat resistance, and the like under the interaction of benzocyclobutenyl cyclotriphosphazene and a hydrocarbon resin. When the resin composition for copper-clad laminates is applied to copper-clad laminates, the copper-clad laminates can be endowed with excellent flame retardant properties, dielectric properties, heat resistance, mechanical properties, and the like.
[0005] The present invention is achieved through the following technical solutions:
[0006] A resin composition for a benzocyclobutenylcyclotriphosphazene copper-clad laminate, comprising the following components in parts by weight:
[0007] 20 to 33 parts of benzocyclobutenyl cyclotriphosphazene, 67 to 80 parts of hydrocarbon resin, 0.0 to 0.22 parts of initiator, 25 to 53 parts of filler, and a first solvent comprising 34 wt% to 36 wt% of the total weight of the benzocyclobutenyl cyclotriphosphazene, hydrocarbon resin, and filler;
[0008] Wherein, the chemical structure of the benzocyclobutenyl cyclotriphosphazene is shown in formula (I); the chemical structure of the hydrocarbon resin is shown in formula (II);
[0009]
[0010] In formula (II), k is any integer from 1 to 100, and j and n are any integers from 0 to 100;
[0011] R1, R3, R4, R5, R6, R7, R8, R9, R 10 Each independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group;
[0012] R2 is an alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms or an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms.
[0013] As some possible implementation methods of the present application, the initiator is any one of dicumyl peroxide (DCP for short), di-tert-butyl peroxide (DTBP for short), and tert-butyl perbenzoate (CP-01 for short).
[0014] As some possible implementation methods of the present application, the filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate, and kaolin.
[0015] As some possible implementation methods of the present application, the first solvent is any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.
[0016] As some possible implementation methods of the present application, the preparation method of the benzocyclobutenyl cyclotriphosphazene is as follows:
[0017] Under a nitrogen atmosphere, hexachlorocyclotriphosphazene, 4-hydroxybenzocyclobutene, and a second solvent are added to a reaction flask in a molar ratio of 1:6:5.5-13. The mixture is stirred and mixed at room temperature. A 1.05-1.5 molar amount of an acid-binding agent is then added. The mixture is reacted at room temperature for 3-6 hours, then heated to 65-90°C for 5-8 hours. After the reaction, the mixture is washed with pure water until the pH reaches 7. Benzocyclobutenyl cyclotriphosphazene is obtained by vacuum distillation. The purity of the prepared product is ≥96%.
[0018] In some embodiments of the present application, the second solvent includes but is not limited to toluene, xylene, butanone or methyl isobutyl ketone.
[0019] As some possible implementation methods of the present application, the acid binding agent includes but is not limited to sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, tetrahydrofuran, trimethylamine, and triethylamine.
[0020] As some possible implementation methods of the present application, the method for preparing benzocyclobutenyl cyclotriphosphazene also includes a phase transfer catalyst, which includes but is not limited to tetrabutylammonium bromide, benzyltriethylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, crown ether, and polyethylene glycol; or includes a polar solvent that can promote the miscibility of the two phases, which includes but is not limited to acetonitrile, N,N'-dimethylformamide, and N,N'-dimethylacetamide.
[0021] In addition, to achieve the above-mentioned purpose, the present invention also provides a method for preparing a benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates, comprising uniformly mixing benzocyclobutenyl cyclotriphosphazene, a hydrocarbon resin, an initiator, a filler and a first solvent to obtain a resin composition.
[0022] Furthermore, to achieve the above-mentioned purpose, a benzocyclobutenyl cyclotriphosphazene copper clad laminate resin composition is used in the preparation of a halogen-free flame-retardant copper clad laminate. The preparation method of the halogen-free flame-retardant copper clad laminate is as follows:
[0023] S1: preparing a resin composition for copper clad laminate into a resin glue, arranging glass fibers in the resin glue, immersing the glass fibers in the resin glue, taking the fibers out, hanging the glass fibers at room temperature to remove most of the solvent, and then baking the glass fibers in an oven at 130° C. to 170° C. for 4 to 7 minutes to obtain a halogen-free flame-retardant prepreg.
[0024] S2: Lay several layers of prepreg together, attach copper foil on both sides, place them in a hot press at 150-170°C, gradually increase the pressure to 0.2-4MPa depending on the glue flow, press for 0.5-1h, then gradually increase the temperature to 195-210°C and hot press for 4-8h, then naturally cool and release the pressure to obtain a halogen-free flame-retardant copper clad laminate. There is no limit to the number of layers of prepreg, and any number of layers can be selected within the process achievable range.
[0025] As some possible implementation methods of the present application, the glass fiber cloth model is selected from 1080E, 2116, 2313, 3313, and 7628.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] 1. The benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates of the present invention comprises benzocyclobutenyl cyclotriphosphazene, which has six copolymerizable benzocyclobutenyl groups. After curing with a hydrocarbon resin, the composition can increase the crosslinking density of the hydrocarbon resin cured product and enhance the rigidity of the molecular structure, thereby improving the heat resistance, mechanical strength, and dimensional stability of the hydrocarbon resin cured product.
[0028] 2. The benzocyclobutenyl cyclotriphosphazene contained in the resin composition for copper-clad laminates of the present invention has a phosphorus content of about 27.7 wt% and a nitrogen content of 12.5 wt%, which can achieve efficient phosphorus-nitrogen synergistic flame retardancy. Compared with flame retardants such as phosphorus-containing phenolic resins and phosphorus-containing epoxy resins, the halogen-free flame retardant properties of the material can be achieved at a smaller addition amount.
[0029] 3. The benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates of the present invention comprises a hydrocarbon resin and a benzocyclobutenyl group. The benzocyclobutenyl cyclotriphosphazene and the hydrocarbon resin are cross-linked and cured. The resulting cured product has the structural characteristics of the hydrocarbon resin and the benzocyclobutenyl group, and can provide the benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates with good flame retardancy, dielectric properties, heat resistance, mechanical properties, etc. The copper-clad laminate prepared using the benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates provided by the present invention has a flame retardancy that can reach UL94 V0 level and has excellent comprehensive properties: a dielectric constant of 2.49-2.53 and a dielectric loss of 0.0010-0.0013 at 10 GHz; a glass transition temperature of 209-221° C., a peel strength of 1.41-1.47 N / mm, and a coefficient of thermal expansion (CTE) of less than 50 ppm.
[0030] 4. The preparation process of the present invention is easy to operate, and the prepared benzocyclobutenyl cyclotriphosphazene resin composition for copper-clad laminates is suitable for the field of high-performance printed circuit boards and has strong practicality. DETAILED DESCRIPTION
[0031] Part I Preparation of Benzocyclobutenyl Cyclotriphosphazene
[0032] Example 1-1
[0033] Under a nitrogen atmosphere, 1 mol of hexachlorocyclotriphosphazene, 6 mol of 4-hydroxybenzocyclobutene, and 10 mol of toluene were added to a reaction flask in sequence. After stirring and mixing at room temperature, 1.08 mol of triethylamine was added. The mixture was reacted for 4 h at room temperature, and the temperature was raised to 70°C and the reaction was continued for 7 h. After the reaction, the mixture was washed with pure water to a pH of 7. The solvent was distilled under reduced pressure to obtain Example 1-1 benzocyclobutenyl cyclotriphosphazene with a purity of 97.5%.
[0034] Example 1-2
[0035] Under a nitrogen atmosphere, 1 mol of hexachlorocyclotriphosphazene, 6 mol of 4-hydroxybenzocyclobutene, 0.008 mol of tetrabutylammonium bromide, and 10 mol of toluene were added to a reaction flask in sequence. After stirring and mixing at room temperature, 1.08 mol of triethylamine was added. The mixture was reacted at room temperature for 4 h, then heated to 70°C and continued to react for 7 h. After the reaction, the mixture was washed with pure water until the pH reached 7. The solvent was distilled off under reduced pressure to obtain Example 1-2 benzocyclobutenyl cyclotriphosphazene with a purity of 98%.
[0036] Examples 1-3
[0037] Under a nitrogen atmosphere, 1 mol of hexachlorocyclotriphosphazene, 6 mol of 4-hydroxybenzocyclobutene, 0.5 mol of N,N'-dimethylformamide, and 13 mol of toluene were added to a reaction flask in sequence. After stirring and mixing at room temperature, 1.1 mol of potassium carbonate was added. The mixture was reacted at room temperature for 6 h, then heated to 75°C and continued to react for 8 h. After the reaction, the mixture was washed with pure water until the pH reached 7. The solvent was distilled off under reduced pressure to obtain Example 1-3 benzocyclobutenyl cyclotriphosphazene with a purity of 97.8%.
[0038] Among them, in Example 1-1, no phase transfer catalyst was added, in Example 1-2, a phase transfer catalyst was added, and in Example 1-3, a polar solvent that promoted phase dissolution was added. All three methods were able to prepare products with relatively high purity.
[0039] Part II Preparation of Halogen-Free Flame-Retardant Hydrocarbon Resin-Based Copper Clad Laminates (Examples 2-6)
[0040] The steps of preparing the resin composition for benzocyclobutenyl cyclotriphosphazene copper clad laminate and the halogen-free flame retardant hydrocarbon resin-based copper clad laminate are as follows:
[0041] 20 to 33 parts by weight of benzocyclobutenyl cyclotriphosphazene, 67 to 80 parts by weight of hydrocarbon resin, 0.01 to 0.22 parts by weight of initiator, 25 to 53 parts by weight of filler, and a second solvent accounting for 34% to 36% of the total weight of the benzocyclobutenyl cyclotriphosphazene, hydrocarbon resin, and filler are uniformly mixed to form a resin adhesive, glass fiber is arranged in the resin adhesive, immersed in the resin adhesive, taken out, hung at room temperature to remove most of the solvent, and then baked in an oven at a temperature of 130° C. to 170° C. for 4 to 7 minutes to prepare a halogen-free flame retardant prepreg sheet.
[0042] Subsequently, several layers of semi-cured sheets are stacked and copper foil is attached on both sides. They are placed in a hot press at a temperature of 150-170°C. Depending on the glue flow, the pressure is gradually increased to 0.2-4MPa and pressed for 0.5-1h. The temperature is then gradually increased to 195-210°C and hot pressed for 4-8h. After natural cooling and pressure relief, the halogen-free flame-retardant copper clad laminate is obtained.
[0043] The components and specific amounts of the halogen-free flame-retardant hydrocarbon resin-based copper clad laminates of Examples 2 to 6 are shown in Table 1.
[0044] Table 1:
[0045]
[0046] The raw materials used in each example in Table 1 are as follows:
[0047] The benzocyclobutenyl cyclotriphosphazene used in Examples 2 to 6 has the general chemical structure shown in Formula (I):
[0048]
[0049] The hydrocarbon resin used in Examples 2 and 3 is polybutadiene Ricon 130, with a vinyl content of 20 wt% to 35 wt%;
[0050] The hydrocarbon resin used in Example 4 is polybutadiene Ricon 142, with a vinyl content of 55 wt%;
[0051] The hydrocarbon resin used in Example 5 is polybutadiene Ricon 153, with a vinyl content of 85 wt%;
[0052] The hydrocarbon resin used in Example 6 is a butadiene-styrene copolymer Ricon 153 with a vinyl content of 20 wt% to 40 wt%;
[0053] The initiator used in Examples 2 to 6 was dicumyl peroxide (DCP), produced by Hong Baoli Group Co., Ltd.
[0054] The filler used in Examples 2 to 6 was silicon dioxide, Jiangsu Lianrui DQ1040;
[0055] The second solvent used in Examples 2 to 6 was butanone.
[0056] Comparative Example 1
[0057] 100 parts by mass of polybutadiene resin (Crayville Ricon 130, vinyl content 20wt% to 35wt%), 38 parts by mass of silicon dioxide, 0.2 parts by mass of dicumyl peroxide and (appropriate amount) of solvent were uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminates having a solid content of 64% to 66%. The glass fiber was arranged in the resin glue and impregnated and then taken out. Most of the solvent was removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C to 170°C for 4 to 7 minutes to obtain a prepreg. 10 layers of prepregs were stacked, and copper foil was attached on both sides. The prepregs were placed in a hot press at a temperature of 150 to 170°C, and the pressurization was gradually increased to 0.2 to 4 MPa (depending on the flow of glue), pressed for 0.5 to 1h, and then gradually heated to 195 to 210°C for hot pressing for 4 to 8h, and then naturally cooled and depressurized to obtain a copper clad laminate of Comparative Example 1.
[0058] Comparative Example 2
[0059] 100 parts by mass of polybutadiene resin (Crayville Ricon153, vinyl content 85wt%), 41 parts by mass of silica, 0.15 parts by mass of dicumyl peroxide and (appropriate amount) of solvent were uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminates having a solid content of 64% to 66%. The glass fiber was arranged in the resin glue and impregnated and then taken out. Most of the solvent was removed by hanging at room temperature, and then placed in an oven at a temperature of 130°C to 170°C for 4 to 7 minutes to obtain a prepreg. 10 layers of prepregs were stacked, and copper foil was attached on both sides. The prepregs were placed in a hot press at a temperature of 150 to 170°C, and the pressurization was gradually increased to 0.2 to 4 MPa (depending on the flow of glue), pressed for 0.5 to 1h, and then gradually heated to 195 to 210°C for hot pressing for 4 to 8h. The prepregs were then naturally cooled and depressurized to obtain a copper clad laminate of Comparative Example 2.
[0060] Comparative Example 3
[0061] Under a nitrogen atmosphere, 1 mol of hexachlorocyclotriphosphazene, 6.5 mol of 4-hydroxybenzocyclobutene, and 12 mol of toluene were added to a reaction flask in sequence, stirred and mixed at room temperature, and then 1.2 mol of triethylamine was added. The reaction was carried out at room temperature for 4 h, and the temperature was raised to 70°C and the reaction was continued for 7 h. After the reaction was completed, the reaction was washed with pure water to pH = 7, and the solvent was distilled under reduced pressure to obtain Comparative Example 3 benzocyclobutenyl cyclotriphosphazene with a purity of 93.7%.
[0062] Take 33 parts by mass of benzocyclobutenyl cyclotriphosphazene prepared in Comparative Example 3, 57 parts by mass of polybutadiene resin (Crayville Ricon 153, vinyl content 85 wt%), 37 parts by mass of silicon dioxide, 0.17 parts by mass of diisopropylbenzene peroxide and (appropriate amount) of solvent and stir and mix them evenly to prepare an epoxy resin composition resin glue for copper clad laminate with a solid content of 64% to 66%. Arrange the glass fiber in the resin glue and immerse it, then take it out and hang it at room temperature. Most of the solvent was removed, and the product was placed in an oven at a temperature of 130°C to 170°C and baked for 4 to 7 minutes to obtain a prepreg. Ten layers of prepregs were stacked, and copper foil was attached on both sides. The product was placed in a hot press at a temperature of 150 to 170°C, and the pressure was gradually increased to 0.2 to 4 MPa (depending on the glue flow) for 0.5 to 1 hour. The product was then gradually heated to 195 to 210°C and hot-pressed for 4 to 8 hours. The product was then naturally cooled and depressurized to obtain the copper clad laminate of Comparative Example 3.
[0063] Comparative Example 4
[0064] Under a nitrogen atmosphere, 1 mol of hexachlorocyclotriphosphazene, 5.7 mol of 4-hydroxybenzocyclobutene, and 12 mol of toluene were added to a reaction flask in sequence, stirred and mixed at room temperature, and then 1.2 mol of triethylamine was added. The reaction was carried out at room temperature for 4 h, and the temperature was raised to 90 ° C. and the reaction was continued for 6 h. After the reaction was completed, the reaction was washed with pure water to pH = 7. After the solvent was distilled under reduced pressure, the comparative example 4 benzocyclobutenyl cyclotriphosphazene was obtained with a purity of 92.3%.
[0065] Take 26 parts by mass of benzocyclobutenyl cyclotriphosphazene prepared in Comparative Example 4, 74 parts by mass of polybutadiene resin (Crayville Ricon 153, vinyl content 85 wt%), 37 parts by mass of silicon dioxide, 0.17 parts by mass of diisopropylbenzene peroxide and (appropriate amount) of solvent and stir and mix them evenly to prepare an epoxy resin composition resin glue for copper clad laminate with a solid content of 64% to 66%. Arrange the glass fiber in the resin glue and immerse it, then take it out and hang it at room temperature. Most of the solvent was removed, and the mixture was placed in an oven at a temperature of 130°C to 170°C and baked for 4 to 7 minutes to obtain a prepreg. Ten layers of prepregs were stacked, and copper foil was attached to both sides. The prepregs were placed in a hot press at a temperature of 150 to 170°C, and the pressure was gradually increased to 0.2 to 4 MPa (depending on the glue flow) for 0.5 to 1 hour. The temperature was then gradually increased to 195 to 210°C and hot pressed for 4 to 8 hours. The copper clad laminate of Comparative Example 4 was then obtained by naturally cooling and decompressing.
[0066] Comparative Example 5
[0067] 25 parts by mass of benzocyclobutenyl cyclotriphosphazene prepared in Example 1-1, 48 parts by mass of maleimide resin (4,4'-bismaleimide diphenylmethane), 26 parts by mass of benzoxazine resin (DFE125A, Dongcai Technology), 39 parts by mass of silicon dioxide, 0.03 parts by mass of diisopropylbenzene peroxide and (appropriate amount) of solvent were uniformly stirred and mixed to prepare an epoxy resin composition resin glue for copper clad laminate with a solid content of 64% to 66%. Glass fibers were arranged and immersed in the resin glue. After soaking, take it out, hang it at room temperature to remove most of the solvent, and then place it in an oven at a temperature of 130℃~170℃ for 4~7min to obtain a prepreg; 10 layers of prepregs are stacked, and copper foil is attached on both sides, and placed in a hot press at a temperature of 150~170℃, and (depending on the glue flow) the pressure is gradually increased to 0.2~4MPa, pressed for 0.5~1h, and then gradually heated to 195~210℃ and hot pressed for 4~8h, and then naturally cooled and depressurized to obtain the copper clad laminate of Comparative Example 5.
[0068] In the preparation of benzocyclobutenylcyclotriphosphazene in Comparative Examples 3 and 4, the raw material ratios provided in the present invention were not strictly followed, resulting in low purity of the prepared products.
[0069] The performance parameters of the copper clad laminates prepared in Examples 2 to 6 were compared with those of the copper clad laminates prepared in Comparative Examples 1 to 4. The results are shown in Table 2.
[0070] Table 2:
[0071]
[0072]
[0073] As can be seen from Table 2, the halogen-free flame-retardant copper-clad laminate prepared from the resin composition for copper-clad laminates of benzocyclobutenyl cyclotriphosphazene provided in this application can reach the V0 level in the UL94 test. Compared with Comparative Examples 1 to 5, it is found that Comparative Examples 1 and 2 both use hydrocarbon resins to prepare copper-clad laminates, but the polyolefin structures used are different and the cross-linking density is different. The resulting copper-clad laminates have poor heat resistance and mechanical properties and are not flame retardant. This shows that even if the cross-linking density is increased in the hydrocarbon resin system, the effect of the embodiment cannot be achieved. Comparative Examples 3 to 4 have low purity of benzocyclobutenyl cyclotriphosphazene, and the dielectric properties, peel strength, and heat resistance of the copper-clad laminates obtained are not as good as those of the embodiment. Comparative Example 5 uses a composite press plate of benzocyclobutenyl cyclotriphosphazene with bismaleimide resin and benzoxazine resin. The resin structure has increased polarity and rigidity, which is conducive to improving heat resistance and dimensional stability, but the dielectric properties and toughness are poor, and the overall performance of the plate is not as good as that of the embodiment. The benzocyclobutenyl cyclotriphosphazene contained in the copper clad laminates of Examples 2 to 6 can effectively improve the heat resistance and mechanical properties of hydrocarbon resin-based copper clad laminates while maintaining the dielectric properties of hydrocarbon resin, thereby making the copper clad laminates have excellent dielectric properties.
[0074] The relevant standards used for the technical indicators in Table 2 are as follows:
[0075] Glass transition temperature Tg: measured by dynamic mechanical analysis (DMA) according to the DMA method specified in 2.4.24.4 of IPC-TM-650;
[0076] Dielectric constant Dk and dielectric loss Df: Use the SPDR method to test 10GHz data according to the method specified in IEC 61189-2-721;
[0077] CTE (Z-axis coefficient of thermal expansion): Tested in accordance with the method specified in 2.4.24.5 of IPC-TM-650;
[0078] Peel strength: Test the peel strength of the metal cover layer according to the "thermal stress" experimental conditions in the method specified in 2.4.8 of IPC-TM-650;
[0079] Plate toughness: A drop hammer impact tester is used, with a drop height of 40 cm and a weight of 1 kg. Toughness is evaluated by indicating that the clearer, more elongated, and smaller the cross at the impact point, the better the toughness of the product, indicated by ◎. A more blurred cross with a larger area indicates poorer toughness and greater brittleness, indicated by △. A cross between clear and blurred indicates average toughness, indicated by ○.
[0080] UL 94 flame retardant performance test: measured according to the UL94 vertical burning test method.
[0081] In the above embodiments and comparative examples, the definition of "solid content" is: the percentage of the mass of non-volatile matter in 100g of sample (i.e., epoxy resin composition resin glue for copper clad laminate) after baking in an oven at 125°C for 3 hours, and the solid content finally determined by adding the mass of water solvent is calculated based on the mass of the non-volatile matter.
[0082] In the above embodiments: the percentages used, unless otherwise specified, are all mass (weight) percentages or percentages known to those skilled in the art; the ratios used, unless otherwise specified, are all mass (weight) ratios; and the weight parts may be grams or kilograms.
[0083] In the above embodiments, the process parameters (temperature, time, concentration, pressure, etc.) and the amounts of the components in each step are ranges, and any point can be applied.
[0084] The technical contents not specifically described in the present invention and the above embodiments are the same as the prior art, and the raw materials are all commercially available products.
Claims
1. A benzocyclobutenylcyclotriphosphazene resin composition for copper-clad laminates, characterized in that: It comprises the following components in parts by weight: 20 to 33 parts of benzocyclobutenyl cyclotriphosphazene, 67 to 80 parts of hydrocarbon resin, 0.0 to 0.22 parts of initiator, 25 to 53 parts of filler, and a first solvent comprising 34 wt% to 36 wt% of the total weight of the benzocyclobutenyl cyclotriphosphazene, hydrocarbon resin, and filler; Wherein, the chemical structure of the benzocyclobutenyl cyclotriphosphazene is shown in formula (I); the chemical structure of the hydrocarbon resin is shown in formula (II); In formula (II), k is any integer from 1 to 100, and j and n are any integers from 0 to 100; R1, R3, R4, R5, R6, R7, R8, R9, R 10 Each independently selected from hydrogen, phenyl, alkyl containing 1 to 10 carbon atoms, aralkyl containing 7 to 12 carbon atoms, ether group containing 1 to 10 carbon atoms and ester group; R2 is an alkyl group containing one unsaturated bond and having 2 to 10 carbon atoms or an aralkyl group containing one unsaturated bond and having 8 to 12 carbon atoms.
2. A benzocyclobutenylcyclotriphosphazene resin composition for copper-clad laminates according to claim 1, characterized in that: The initiator is any one of dicumyl peroxide, di-tert-butyl peroxide, and tert-butyl perbenzoate.
3. The resin composition for copper-clad laminates according to claim 1, wherein: The filler is any one of silicon dioxide, montmorillonite, magnesium oxide, aluminum oxide, mica powder, barium sulfate and kaolin.
4. The resin composition for copper-clad laminates according to claim 1, wherein: The first solvent is any one of acetone, butanone, cyclohexanone, methyl isobutyl ketone, toluene, propylene glycol monomethyl ether, and propylene glycol methyl ether acetate.
5. The resin composition for copper-clad laminates according to claim 1, wherein: The preparation method of the benzocyclobutenyl cyclotriphosphazene is as follows: Under a nitrogen atmosphere, hexachlorocyclotriphosphazene, 4-hydroxybenzocyclobutene, and a second solvent are sequentially added to a reaction flask in a molar ratio of 1:6:5.5-13, stirred and mixed uniformly at room temperature, and then an acid binding agent with a molar amount of 1.05-1.5 is added. The reaction is carried out at room temperature for 3-6 hours, and then the temperature is raised to 65-90°C and the reaction is carried out for 5-8 hours. After the reaction is completed, the mixture is washed with pure water to pH = 7, and then distilled under reduced pressure to obtain benzocyclobutenyl cyclotriphosphazene.
6. The resin composition for copper-clad laminates of claim 5, wherein: The second solvent includes but is not limited to toluene, xylene, methyl ethyl ketone or methyl isobutyl ketone.
7. The resin composition for copper-clad laminates according to claim 5, wherein: The acid binding agent includes but is not limited to sodium hydroxide, potassium hydroxide, potassium carbonate, sodium carbonate, sodium bicarbonate, potassium bicarbonate, tetrahydrofuran, trimethylamine, and triethylamine.
8. The resin composition for copper-clad laminates according to claim 5, wherein: The method for preparing benzocyclobutenyl cyclotriphosphazene further includes a phase transfer catalyst, which includes but is not limited to tetrabutylammonium bromide, benzyltriethylammonium bromide, tetrabutylammonium chloride, tetrabutylammonium hydrogen sulfate, crown ether, and polyethylene glycol; or a polar solvent that can promote the miscibility of the two phases, which includes but is not limited to acetonitrile, N,N'-dimethylformamide, and N,N'-dimethylacetamide.
9. The method for preparing a resin composition for copper-clad laminates of benzocyclobutenylcyclotriphosphazene according to any one of claims 1 to 8, wherein: Benzocyclobutenyl cyclotriphosphazene, hydrocarbon resin, initiator, filler and first solvent are uniformly mixed to obtain a resin composition.
10. Use of a benzocyclobutenylcyclotriphosphazene copper-clad laminate resin composition according to any one of claims 1 to 8 in preparing a halogen-free flame-retardant copper-clad laminate, characterized in that: The preparation method of the halogen-free flame-retardant copper clad laminate is as follows: S1: preparing a resin composition for copper clad laminate into a resin glue, arranging glass fibers in the resin glue, immersing the glass fibers in the resin glue, taking the fibers out, hanging the glass fibers at room temperature to remove most of the solvent, and then baking the glass fibers in an oven at 130° C. to 170° C. for 4 to 7 minutes to obtain a halogen-free flame-retardant prepreg. S2 stacks several layers of semi-cured sheets and attaches copper foil on both sides. Place them in a hot press at a temperature of 150-170°C. Depending on the glue flow, gradually increase the pressure to 0.2-4MPa and press for 0.5-1h. Then gradually increase the temperature to 195-210°C and hot press for 4-8h. After natural cooling and pressure relief, the halogen-free flame-retardant copper clad laminate is obtained.
Citation Information
Cited By
Cyclophosphazene reactive flame retardant containing benzocyclobutene group, and preparation method therefor and use thereof
WO2026103579A1